2020
DOI: 10.1002/ajmg.a.61748
|View full text |Cite
|
Sign up to set email alerts
|

Complete blood count differences in a cohort of Down syndrome neonates with transient abnormal myelopoiesis screened for GATA1 pathogenic variants

Abstract: Transient abnormal myelopoiesis (TAM) raises the risk for acute myeloid leukemia of Down syndrome (DS) (ML‐DS), and both are related to GATA1 pathogenic variants. Here, we analyzed which findings on complete blood count (CBC) are associated with TAM in a cohort of neonates with DS screened for GATA1 pathogenic variants. The CBCs were compared among 70 newborns with DS, including 16 patients (22.9%) with TAM (cases), and 54 patients (77.1%) without TAM (controls). TAM was defined as peripheral circulating blast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As the WHO does not specify the percentage of blasts to define TAM, different groups use different blast percentages ranging from ≥1% to ≥10% to define TAM in neonates with DS [6][7][8][9]. Therefore, we defined TAM as either >5% blasts (as determined by immunophenotyping or morphology), and/or detection of a GATA1 mutation.…”
Section: To the Editormentioning
confidence: 99%
“…As the WHO does not specify the percentage of blasts to define TAM, different groups use different blast percentages ranging from ≥1% to ≥10% to define TAM in neonates with DS [6][7][8][9]. Therefore, we defined TAM as either >5% blasts (as determined by immunophenotyping or morphology), and/or detection of a GATA1 mutation.…”
Section: To the Editormentioning
confidence: 99%
“…Most notably, normal WBC count, hemoglobin, and MCV values decrease as neonates' age from infancy to 2 years old; therefore, the apparent macrocytosis and leukocytosis observed in TAM babies are likely due to physiologic CBC values rather than the myeloid pathology [10]. Prior studies have evaluated TAM CBC values compared to non-TAM patients with DS and showed no statistically significant difference with the exception of lymphocytosis identified in TAM [11]. Conversely, ML-DS was characterized by presentation at older age and with median hemoglobin and platelet values below what is considered normal for age, indicating that the anemia and thrombocytopenia seen in these patients was secondary to the underlying myeloid neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Both of the variations c.220G > A and c.49dupC are absent in the general population according to public databases (gnomAD, 1000 Genomes Project, and Exome Aggregation Consortium). Mutation c.220G > A has been reported in several research as pathogenic according to the ACMG guideline [29][30][31] . At the same amino acid c.220G > C (p.Val74Leu) change has been previously reported as pathogenic in the ClinVar database.…”
Section: Discussionmentioning
confidence: 99%
“…At the same amino acid c.220G > C (p.Val74Leu) change has been previously reported as pathogenic in the ClinVar database. The consequence of the base c.220G > A substitution was a splice mutation that changed the amino acid sequence Val74Ile 29 .Also at the same amino acid c.49_50del (p.Gln17fs) and c.49C > T (p.Gln17Ter) already provide to be pathogenic in the ClinVar database. Cabelof, DC et al 32 and Kanezaki R et al 33 reported c.49 C > T in their case 10 and case 5, respectively.…”
Section: Discussionmentioning
confidence: 99%